Cochrane, John H. The Fiscal Theory of the Price Level - Nunes, Ricardo (Journal of Economic Literature, 2025)
Ricardo Nunes of University of Surrey, CIMS, and CfM reviews “The Fiscal Theory of the Price Level” by John H. Cochrane. The Econlit abstract of this book begins: “Considers ways to make fiscal theory accessible, developing stories and intuition for how it can help facilitate an understanding of the world. Explores a simple two-period fiscal theory model with perfectly flexible prices, constant interest rates, short-term debt, and no risk premiums, in addition to a simple intertemporal model.”